Community Views On Polygamy And Polyandry Islamic Legal Perspective - Maswandi, Maswandi (International Asia Of Law and Money Laundering (IAML), 2023)
Writing this article aims to determine the legal basis of polygamy and polyandry in Islamic law and positive law in Indonesia and the impact of polygamy and polyandry. In this paper using normative juridical approach with various theories of interpretation. Religious court is a judicial institution under the Supreme Court which is very important in dealing with issues regarding disputes related to the religion of Islam. Start from marriage, inheritance, wills, grants, Waqf, zakat, Infaq, Sadaqah, to sharia economy being the duty and authority of the Religious Court in accordance with articles 49 and 50 of Law No.7 Year 1989 on religious courts which has been amended by law No.3 of 2006. In Article 4 paragraph (1) of Law No. 1 of 1974 on marriage, if a husband wants to marry more of a person is obliged to apply to the court in the area of his residence (that is, the Religious Court). Also regulated in the next articles in the submission of polygamy must meet the requirements that have been determined according to the Marriage Act. Regulation on polygamy in positive law seems to make it difficult for husbands to polygamy, while Islamic law itself is not too make it difficult for a husband to polygamy. Therefore, these two laws must be in sync with each other in order to it does not cause a problem in marriage, especially polygamy and what has no rules but occurs is polyandry.